Rebound Mechanism and Control of the Hard Main Roof in the Deep Mining Roadway in Huainan Mining Area - Denghong Chen; Chao Li; Xinzhu Hua; Xiaoyu Lu; Yongqiang Yuan; Chen Li (Shock and Vibration)
Taking the occurrence conditions of the hard main roof in the deep 13-1 coal mining roadway in Huainan mining area as the research object, based on the mechanical parameters of the surrounding rock and the stress state of the main roof obtained by numerical simulation, a simply supported beam calculation model was established based on the damage factor D, main roof support reaction RA, RB, and critical range C (9 m) and B (7 m) at the elastoplastic junction of the solid coal side and mining face side (hereinafter referred to as “junction”). Considering that the damage area still has a large bearing capacity, the vertical stress of the main roof at the junction is K1γH (0.05γh, 0.15γh, and 0.25γh) and K2γH (0.01γh, 0.10γh, and 0.2γh). The maximum deflection is 21 mm, 324 mm, and 627.6 mm, respectively. According to the criterion of tensile failure, the maximum bending moment of the top beam is 209 mN·m at the side of the working face 3.1 m away from the roadway side when K1 = 0.15 and K2 = 0.10, and the whole hard main roof is in tensile failure except the junction. To control the stability of the top beam and simplify the supporting reaction to limit the deformation of the slope angle, RC and RD are used to construct the statically indeterminate beam. By adding an anchor cable and advance self-moving support to the roadway side angle, the problem of difficult control of the surrounding rock with a large deformation of the side angle roof is solved, which provides a reference for roof control under similar conditions.